Apparent paradox of neurohumoral axis inhibition after body fluid volume depletion in patients with chronic congestive heart failure and water retention. Issue 6 (December 1994) - Guazzi, M D; Agostoni, P; Perego, B; Lauri, G; Salvioni, A; Giraldi, F; Matturri, M; Guazzi, M; Marenzi, G
Abstract : BACKGROUND--Hypovolaemia stimulates the sympathoadrenal and renin systems and water retention. It has been proposed that in congestive heart failure reduction of cardiac output and any associated decrease in blood pressure cause underfilling of the arterial compartment, which promotes and perpetuates neurohumoral activation and the retention of fluid. This study examined whether an intravascular volume deficit accounts for patterns that largely exceed the limits of a homoeostatic response, which are sometimes seen in advanced congestive heart failure. METHODS AND RESULTS--In 22 patients with congestive heart failure and water retention the body fluid mass was reduced by ultrafiltration and the neurohumoral reaction was monitored. A Diafilter, which was part of an external venous circuit was regulated to produce 500 ml/hour of ultrafiltrate (mean (SD) 3122 (1199) ml) until right atrial pressure was reduced to 50% of baseline. Haemodynamic variables, plasma renin activity, noradrenaline, and aldosterone were measured before and within 48 hours of ultrafiltration. After ultrafiltration, which produced a 20% reduction of plasma volume and a moderate decrease in cardiac output and blood pressure (consistent with a diminished degree of filling of the arterial compartment), there was an obvious decrease in noradrenaline, plasma renin activity, and aldosterone. In the next 48 hours plasma volume, cardiac output, and blood pressure recovered; the neurohumoral axis was depressed; and there was a striking enhancement of water and sodium excretion with resolution of the peripheral oedema and organ congestion. The neurohumoral changes and haemodynamic changes were not related. There were significant correlations between the neurohumoral changes and increase in urinary output and sodium excretion. CONCLUSIONS--In advanced congestive heart failure arterial underfilling was not the main mechanism for activating the neurohumoral axis and retaining fluid. Because a decrease in circulating hormones was associated with reabsorption of extravascular fluid it is likely that hypoperfusion and/or congestion of organs, such as the kidney and lung, reduce the clearance of circulating noradrenaline and help to keep plasma concentrations of renin and aldosterone raised. A positive feedback loop between fluid retention and plasma hormone concentrations may be responsible for progression of congestive heart failure.